School Cooperatives as a Way to Promote the Associative Entrepreneurial Capacity of Children and Youth [Cooperativas Escolares Como Una Forma de Fomentar la Capacidad Emprendedora Asociativa de Niños y Jóvenes] - Radrigan-Rubio, M (Universidad Compultense Madrid, 2020)
This article corresponds to the systematization of a historical experience of almost 20 years of promotion of the model of school cooperatives in Chile, which began in 1998 with the support of the Cooperativa de Ahorro y Crédito COOPEUCH, and which was initially promoted by the Program Interdisciplinary of Associative Studies, PROASOCIA, of the University of Chile and later by the International Social Economy Center of the University of Santiago de Chile, which has always had the purpose of bringing the cooperative business model to the new generations that are immersed in the school environment, and that in this way they can experience directly and practically a socially oriented entrepreneurial initiative. This article presents the first longitudinal systematization that is carried out of this initiative and that also reflects on the different critical dimensions that relate to this type of experiences, such as, for example, the age of the participants, the level of involvement of the directors of the schools, the relation with the school curriculum and the perceptions that the own students have of their own initiatives, generating with them recommendations for the impulse of the processes of promotion of the emprendimiento at scholastic level. © 2020 Universidad Complutense de Madrid. All rights reserved.
Keywords: Entrepreneurship; School curriculum; Cooperativism; School; Youth; Childhood